The Emergence of Theology and the Parting of the Ways (Teología, 2020)
With this article in two parts I hope to open up an examination of the role played by the fourth-century Trinitarian controversies in the late ancient estrangement between Jews and Christians. The article proposes that new partitions emerged in Judaeo-Christianity thanks to the novel practices that during the Trinitarian controversies Christians developed to express their ideas about God. From the viewpoint of theological content, the Trinitarian disputes persisted within a lasting Christian-Jewish continuum: none of the theological options explored by Christianswould have caused particular scandal to a contemporaneous Jew on account of its particular articulation of divine reality. Nevertheless, by disengaging from earlier  modes of argumentation functioning as bridges between proto-rabbinic and proto-Christian discourses, the production of a theological field on the part of believers in Jesus was largely responsible for the separate constitution of Christianity and Judaism as intellectual traditions.
Keywords: Trinitarian Controversies; Judaism; Christianity; Nicea; Rabbinism